2021
DOI: 10.1057/s41599-021-00718-9
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric study of research topics, collaboration, and centrality in the iterated prisoner’s dilemma

Abstract: This manuscript explores the research topics and collaborative behaviour of authors in the field of the Prisoner’s Dilemma using topic modeling and a graph theoretic analysis of the co-authorship network. The analysis identified five research topics in the Prisoner’s Dilemma which have been relevant over the course of time. These are human subject research, biological studies, strategies, evolutionary dynamics on networks and modeling problems as a Prisoner’s Dilemma game. Moreover, the results demonstrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 64 publications
0
20
0
1
Order By: Relevance
“…If two or more research themes are equivalent in their degree centrality, the one with the most significant betweenness centrality is regarded to have the most impact. The greater the betweenness centrality value, the higher the chance of a node in the network being on the shortest path between nodes (Gephi, 2017; Glynatsi and Knight 2021 ). The most important research themes and their connectedness, as demonstrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…If two or more research themes are equivalent in their degree centrality, the one with the most significant betweenness centrality is regarded to have the most impact. The greater the betweenness centrality value, the higher the chance of a node in the network being on the shortest path between nodes (Gephi, 2017; Glynatsi and Knight 2021 ). The most important research themes and their connectedness, as demonstrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Game theory itself has a number of subfields and the one considered in this tutorial is the area of repeated games. Repeated games have been the subject of research (Axelrod & Hamilton, 1981;Glynatsi & Knight, 2021;Nowak, 2006) but have also been used extensively as an entry to the subject for students at undergraduate level courses (Brokaw & Merz, 2004;Knight, 2015). This tutorial focuses on the Iterated Prisoner's Dilemma.…”
Section: Statement Of Needmentioning
confidence: 99%
“…Glynatsi et al, (2021). Game Theory and Python: An educational tutorial to game theory and repeated games using Python.…”
mentioning
confidence: 99%
“…This reputation-based mechanism for the evolution of cooperation is referred to as indirect reciprocity 11 14 . In contrast to direct reciprocity 15 18 , which is based on repeated interactions between the same players, indirect reciprocity does not require any two individuals to interact with one another more than once. Instead it only requires population members to continually assess each others’ actions, and to act based on these reputations.…”
Section: Introductionmentioning
confidence: 99%